The right to learn : educational strategies for socially excluded youth in Europe - Nicaise, Ides (Policy Press, 2000)
This book reports on a wide-ranging research study into education and social exclusion in Europe. It explores differing strategies to improve educational success among disadvantaged children. The countries studied, UK, Ireland, Belgium, The Netherlands, Portugal and Spain, reflect the diversity in systems and policies that currently exist. The book assesses their relative success, and makes suggestions for good practice.